EFEKTIVITAS PELAKSANAAN E-LEARNING BAGI BASE STATION SUBSYSTEM (BSS) ENGINEER DI LINGKUNGAN PT TELKOMSEL INDONESIA - Hanafi, Agustina (Journal of Management and Business Review, 2016)
Objectives on this research is to find out sveral variables affecting effectiveness on e-learning programme conducted by PT Telkomsel Indonesia for its Base Station Subsystem Engineer. Using Computer Based Instruction approaching model from Lowe et all,2005 (A theory of effective computer-based instruction for adults) combined with integrated model of training evaluation and effectivenes from Alvarez et all, 2010, construct of his research was built. By means of those model, some hypotheses has been made: individual characteristics of learner, organizational characteristics and in the same tie those three variables causality related to e-learning effectiveness. Method used in this research is descriptive and assosiative research to describe samples behaviour wihtin research framework as well as finding out correlation among independent variables to dependent one. Using 100 BSS engineer all over Telkomsel area, results of this research proves that there are significant correlations among three variables above to elearning effectiveness conducted by PT. Telkomsel Indonesia and causality of variables can be proved